Pendekatan Ekonomi Kreatif Terhadap Pertumbuhan Ekonomi - Sri Wahyuningsih; Dede Satriani (LPPM ISNJ Bengkalis, 2019)
This study aims to determine how much influence the creative economy approach has on economic growth. Based on the results of the hypothesis tested the influence of the creative economy on economic growth was rejected. This has been proven from the results of simple linear regression testing which shows that the influence of the creative economy on economic growth is weak. It can be understood that the creative economy in the village of Pedekik is engaged in the business of creative industries still lacking new innovations, creativity and new inventions so that they can compete with market developments. Indeed the creative economy will slowly replace the role of commodities and natural resources as a supporter of the Indonesian economy. This study shows the results that there is no influence on the creative economy on economic growth.